Penerapan MOORA dalam Pedukung Keputusan Kelayakan Penerimaan Bantuan Program Keluarga Harapan (PKH) - Adisyahputra Manik (STMIK Budi Darma, 2020)
The economy that is happening in Indonesia is not balanced because of the large economic disparity between one region and another, this can be seen clearly from the uneven income of the people and the poverty problems that occur in terms of clothing, food and shelter. The community has the right to get proper clothing, food and shelter for the sake of creating a prosperous society. If one of them is still not fulfilled, then prosperity will not be achieved. To realize this, the government has held various poverty reduction programs, one of which is in the form of social funds provided to the poor. Problems that often occur in determining the eligibility of receiving assistance. The assessment process of the beneficiary community in Tuhtuhan Village is not yet perfect, only covering the type of work, total income, number of dependents and age. This method of assessment is subjective, which can lead to social jealousy for those who do not accept it. From the above problems, it can be solved by utilizing computer technology to create a Decision Support System (DSS). One of them is by using the Moora method. The MOORA (Multi Objective Optimization on the Basis of Ratio Analysis) method is applied to solve many economic, managerial and construction problems. math formula calculations with exact results